Vibration Test and Analysis of the Internal Parallel Move Gear Reducer based on Virtual Instrument - Chen Xiao (Jixie chuandong)
For the vibration test problem of internal parallel move gears reducer,the vibration test and analysis system of internal parallel moving gear reducer based on virtual instrument is proposed,through the test,the feasibility and correctness of the system are verified. The test results show that,the vibration amplitude of measuring points is proportional to the speed. Under the same speed in different load situation,the maximum amplitude is basic not variable,but the quadratic mean is obviously of increased. Under all conditions,the vibration signal is all taking the times frequency of the entered axis gear and shunt gear meshing frequency as mainly vibration frequency,and taking the 3 times frequency of power frequency as the intervals. The vibration rules of the reducer at X axis and Y axis direction are roughly to be the same,the cause of differences is the different of the structure distribution of X,Y direction.